2007
DOI: 10.1210/me.2007-0055
|View full text |Cite
|
Sign up to set email alerts
|

GPR39 Splice Variants Versus Antisense Gene LYPD1: Expression and Regulation in Gastrointestinal Tract, Endocrine Pancreas, Liver, and White Adipose Tissue

Abstract: G protein-coupled receptor 39 (GPR39) is a constitutively active, orphan member of the ghrelin receptor family that is activated by zinc ions. GPR39 is here described to be expressed in a full-length, biologically active seven-transmembrane form, GPR39-1a, as well as in a truncated splice variant five-transmembrane form, GPR39-1b. The 3' exon of the GPR39 gene overlaps with an antisense gene called LYPD1 (Ly-6/PLAUR domain containing 1). Quantitative RT-PCR analysis demonstrated that GPR39-1a is expressed sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 39 publications
3
85
1
1
Order By: Relevance
“…However, sbGPR39-1b is also expressed in other tissues where there is little sbGPR39-1a, particularly in the brain regions including the hypothalamus and pituitary. A similar tissue expression pattern of GPR39-1b in mouse was reported by Egerod et al (2007). This conserved GPR39-1b expression pattern in mammals and fish implies a possible physiological role of the truncated receptor in these tissues.…”
Section: Tissue Distribution Of Gpr39 Transcripts In Seabreamsupporting
confidence: 78%
See 1 more Smart Citation
“…However, sbGPR39-1b is also expressed in other tissues where there is little sbGPR39-1a, particularly in the brain regions including the hypothalamus and pituitary. A similar tissue expression pattern of GPR39-1b in mouse was reported by Egerod et al (2007). This conserved GPR39-1b expression pattern in mammals and fish implies a possible physiological role of the truncated receptor in these tissues.…”
Section: Tissue Distribution Of Gpr39 Transcripts In Seabreamsupporting
confidence: 78%
“…In the present study, we have clearly demonstrated the presence of two alternatively spliced forms of GPR39 in teleosts as well as in mammals, and that these two receptors in seabream are distinct in biological function and are differentially expressed. During the preparation of this manuscript, Egerod et al (2007) also reported that GPR39-1b transcripts are found in human, mouse, rat, and chicken, further supporting the notion that the presence of two GPR39 transcripts is a general phenomenon among vertebrates.…”
Section: Identification Of An Additional Gpr39-1b Transcript Among Vasupporting
confidence: 69%
“…GPR39 receptor has two splice variants, GPR39-1a and GPR39-1b. GPR39-1a is expressed selectively in the gastrointestinal tract, whereas GPR39-1b has a wider expression pattern, including nuclei in the central nervous system, for example the amygdala, and hippocampus [4]. Later studies reported that GPR39 may not have obestatin as a main ligand [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…GPR39 mRNA has been shown to be expressed in a wide range of tissues in humans, rats, mice and chickens, with relatively higher levels in the liver, kidney, pancreas and gastrointestinal (GI) tract [3,12,13,19,21]. In GPR39-deficient mice, accelerated gastric emptying of a solid meal, body weight gain and high body fat composition have been observed, which suggests that GPR39 plays important roles in digestive and metabolic functions [13].…”
mentioning
confidence: 99%
“…gov/BLAST) showed the presence of an approximately 17.8 kb intron between positions 994 and 995 in the GPR39 cDNA, which indicates that the bovine GPR39 gene consists of 2 exons. Recently, the human GPR39 gene was shown to have a similar exon / intron structure [3].…”
mentioning
confidence: 99%